Private and open data in Asia : a regional guide - Lu, Franklin (O'Reilly Media, 2015)
The rise of big data in recent years coincides with the economic and political rise of Asia, especially among the five countries that make up the bulk of the East Asian Internet-using population: China, Japan, Korea, India, and Indonesia. If you're thinking of entering the Asian market, this O'Reilly report provides an overview of the current state of big data and open data in these countries, and helps you examine whether the benefits of doing business with them outweigh the costs. While Japan and South Korea are highly developed countries with lofty Internet penetration rates, China, India, and Indonesia have enormous populations, relatively low Internet penetration, and enormous growth potential. But access to open data from fields such as healthcare, education, agriculture, transportation, energy, and finance-data vital for building businesses and services-varies from country to country. Each of them has a distinctive character reflecting its national priorities. To help you assess risk vs opportunity in the Asian market, author Franklin Lu reviews these five countries individually to reveal the nature of data privacy laws, open data initiatives, and existing businesses.